Analisis Perkembangan Sosial Anak Usia 5-6 Tahun pada Permainan Balok di TK Ulul Ilmi 2 Medan Marelan - Sindi Silfiya; Dwi Septi Anjas Wulan (Lembaga Pengembangan Kinerja Dosen, 2024)
This study was conducted with the aim of describing the social development of children aged 5-6 years through block games at Ulul Ilmi 2 Kindergarten Medan Marelan. The type of research used is descriptive qualitative. The subjects in this study were the B class consisting of 10 children aged 5-6 years. The data collection technique in the study was by observation. The data analysis technique was carried out through data reduction, data presentation, and drawing conclusions. The validity of the data was tested by process triangulation. The results of the study showed that Children's social development in the empathy aspect for the sub-indicator shows concern for friends when they fail to stack blocks 10% is at a fairly good stage and 90% is at a very good stage. For the sub-indicator of appreciating friends' work 30% is at a good stage, and 70% is at a very good stage. Children's social development in the generosity aspect is 80% at a very good stage and 20% at a good stage. Children's social development in the cooperation aspect is 80% at a very good stage and 20% at a fairly good stage. Children's social development in the concern aspect for the sub-indicator of helping friends who need help 10% is at a fairly good stage and 90% at a very good stage. For the sub-indicator of reassembling blocks 10% is at a fairly good stage.